2000
DOI: 10.1159/000007809
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Zymogen Activation in Human Acute Pancreatitis

Abstract: Background: Activation of trypsinogen and phospholipase A2 is an early event in pancreatic inflammation, but little is known about zymogen activation and the severity of human pancreatitis. Methods: Using a new fluoroimmunoassay we measured trypsinogen activation peptide (TAP) and phospholipase A2 activation peptide (PROP) in plasma and ascites in 25 patients with acute pancreatitis. TAP, PROP, Pro-PROP and pancreatic PLA2-I were measured in plasma for 14 days and in pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…This ratio returned to normal 25-36 h after symptom onset and then rose steadily to similar peak levels over the next 96 h. Comparison with the present study is not possible, because the actual urinary PROP values were not given [12]. Another small clinical study reported that the plasma PROP levels were actually lower in severe as compared with mild acute pancreatitis [13].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This ratio returned to normal 25-36 h after symptom onset and then rose steadily to similar peak levels over the next 96 h. Comparison with the present study is not possible, because the actual urinary PROP values were not given [12]. Another small clinical study reported that the plasma PROP levels were actually lower in severe as compared with mild acute pancreatitis [13].…”
Section: Discussioncontrasting
confidence: 54%
“…Since there have only been two small previous studies of PROP in patients with acute pancreatitis with apparently conflicting results [12,13], we report the findings of a large prospective multicentre study.…”
Section: Introductionmentioning
confidence: 98%
“…It is activated by trypsin in the duodenum. The activation of pro-hG1B by cleavage of the PROP, a heptapeptide of the sequence DSGISPR, is linked to diseases like pancreatitis (8) and acute lung injury (9). Circulating hG1B, mostly in the form of pro-hG1B, indicates pancreatic injury in acute pancreatitis (10).…”
mentioning
confidence: 99%
“…During acute pancreatitis, the conversion of trypsinogen into active trypsin within acinar cells is followed by an activation of several enzymes, such as elastase, phospholipase A 2 and NADPH oxidase [38]. Through the increase of intracellular calcium concentration, elastase and ROS (H 2 O 2 ), NADPH oxidase and phospholipase A 2 are activated [39,40]. Here, it should be considered that glycine inhibits phospholipase A 2 , an event which leads to stabilization of the cell membrane [41].…”
Section: Discussionmentioning
confidence: 99%